Hubungan BMI dan Protein Urine terhadap Hipertensi Ibu Hamil Trimester III di Klinik Marlianti Aceh - Lia Andriani; Nur Azizah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Background: Hypertension in pregnant women in the third trimester is a serious health problem that can have a negative impact on the mother and fetus. The main contributing risk factors are Body Mass Index (BMI) and urine protein levels. This study aims to analyze the relationship between BMI and urine protein to the incidence of hypertension in pregnant women in the third trimester at the Marlianti Clinic, East Aceh.Methods: An analytical observational study with a cross-sectional design. The sample was pregnant women in the third trimester who underwent pregnancy check-ups. Data were collected through BMI measurements and urine protein examinations, then analyzed using bivariate tests.Results: Of the 48 pregnant women with hypertension, 81.3% had a BMI ≥25 compared to 41.7% in the control group. The analysis showed a significant relationship between obesity and hypertension (p < 0.001, OR = 6.0; 95% CI: 2.407-15.291). In addition, 70.8% of mothers with hypertension had positive urine protein compared to 33.3% in the control group (p = 0.001, OR = 4.8; 95% CI: 2.046-11.531).Conclusion: BMI and urine protein levels are significantly associated with hypertension in pregnant women in the third trimester. Monitoring BMI and urine protein is important for the prevention and early treatment of gestational hypertension.